Investigating the effects of pressure support ventilation and positive end-expiratory pressure during extubation on respiratory system complications - Ali Rıza Ata; Dilek Çetinkaya; Ferda Yaman (Perioperative Medicine)
Abstract Background Postoperative extubation is a critical phase. Various medications and different ventilation modes are employed during extubation to minimize potential issues. This study aimed to observe the early effects of the concurrent use of positive end-expiratory pressure (PEEP) and pressure support ventilation (PSV) modes during the extubation-emerge period on the respiratory system. Methods After laparoscopic cholecystectomy, patients were administered a remifentanil infusion following the cessation of inhalation agents. PSV and PEEP modes were used on the mechanical ventilator, and the patients were extubated upon awakening. Hemodynamic and respiratory parameters, as well as complications during intraoperative and extubation periods, were recorded. Results A total of 199 patients were evaluated. Patients with complications were defined as group I (n = 37), and those without complications as group 0 (n = 167). Post-extubation complications included cough (3 or more, persistent or repetitive coughing) in 12 patients (6.04%), desaturation (SPO2 < 90% for 10 s) in nine patients (4.53%), bronchospasm in eight patients (4.02%), agitation (5 and above on the agitation scale) in three patients (1.5%), need for rescue mask ventilation (SPO2 < 90% lasting longer than 10 s) in three patients (1.5%), and airway obstruction (2 and above according to laryngospasm score) in two patients (1%). Statistically significant differences were observed between the two groups for ASA III (p = 0.0365). Conclusions The use of PSV and PEEP modes during extubation-emergence period in laparoscopic cholecystectomy results in a low rate of respiratory system complications, which are mostly minor. These modes can be safely used during the extubation phase. However, since these complications are seen in patients with high ASA physical scores, further studies are needed for these patients. Trial registration NCT06356649.